A Case of Pott's Puffy Tumor from Odontogenic Source - Merrill, Tyler; Davis, Kyle; Gardner, James Reed; Kanaan, Alissa (European Journal of General Dentistry, 2021)
Pott's puffy tumor (PPT) is a known complication of frontal sinusitis. Odontogenic maxillary sinusitis can seldomly spread to involve the frontal sinus but has not been implicated in the development of PPT. Herein, we describe a case of frontal sinusitis originating from an odontogenic source and culminating in PPT.
Keywords: Pott's puffy tumor; odontogenic; sinusitis